Meanings of Emerging Discourses From Kenyas’ Mainstream Press Mediatization of Sino-Kenya Relations: The Meanings of Discourse of the mediatization - Ogweno, Josphat (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2021)
Theoretically, the Kenyan press tends to be superficial in mediatizing Sino-Kenya relations. It is important therefore that the Kenyan mainstream press goes beyond the superficial mediatization of events on Sino-Kenya relations to play both a critical, inclusive, democratic and developmental role that suits the African continent. The tightening, multilevel and overarching social, political and economic relations are to a certain extent dependent on a critical analysis of the Kenyan mainstream press. The relation however is exhibited by the Kenyan mainstream press superficially and therefore the need to have a critical analysis of the selected newspapers. The study used the political economy and the mediatization theories to critically explore and get the discourses in the selected Kenyan Newspapers’ mediatization of Sino-Kenya relations. This study therefore aimed at investigate the meanings of emerging discourses from Kenyas’ mainstream press mediatization of Sino-Kenya relations. The study sought to answer the following question, what are the meanings of emerging discourses from Kenyas’ mainstream press mediatization of Sino-Kenya relations? An explorative research design approach was adopted to address the question of meditization by the mainstream press on Sino-Kenya relations. Triangulation approach was used in the analysis. A two-step purposive sampling method was used in selecting first, the newspapers because they are market leaders and they are the newspapers that covered broadly the relations and then the period of study. The study evaluated three newspapers: The Daily Nation, The Standard and The Star. The study analysed articles in the newspapers between the year 2015 and 2019. Finally, relevant content was sampled that produce a sample size of 70 newspapers and 3 journalists and 3 Chief Editors who were purposefully sampled. Interviews were conducted with key informants and analyzed qualitatively while the coding sheet was used in collecting data then analysed quantitatively to record the frequency of occurrence of the identified nature of mediatization and qualitatively to study the meanings of emerging discourses, use of attributive words, pictures, and discussions and their inherent meanings from the discourses. The identified nature of mediatization were found to be fused with ideological undertones that served in mediatizing the Sino-Kenya relations. The results indicated that articles adopted neutral tone whose implication was a dual beneficial relation. The study suggested that the editorial policies of publishing houses should also be points of focus in future studies and should have a deeper discussion in its contents.